Vestibular schwannoma: anatomical, medical and surgical perspective - Hassan, Ashfaq Ul; Hassan, Ghulam; Rasool, Zahida (International Journal of Research in Medical Sciences, 2017)
The term "acoustic" is a misnomer, as the tumor rarely arises from the acoustic (or cochlear) division of the vestibulocochlear nerve. The correct medical term is vestibular schwannoma, because it involves the vestibular portion of the 8th cranial nerve. They are benign, rather raretumors. They expand in size and grow larger; they can push against the brain. While the tumor does not actually invade the brain, the pressure of the tumor can displace brain tissue.